Editorial: Academic integrity gaining increased attention in Canada (Canadian Perspectives on Academic Integrity, 2018)
We introduce the second issue of our first volume, highlighting the lead article from Amanda McKenzie and offering commentary on how academic integrity issues have gained attention in the national media this year.